2020
DOI: 10.1016/j.ceramint.2020.02.145
|View full text |Cite
|
Sign up to set email alerts
|

The keys to avoid undesired structural defects in nanotubular TiO2 films prepared by electrochemical anodization

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…However, the higher percentage of NH4F reduced the length, which can be caused by the drastic chemical dissolution due to the increased number of fluoride ions on the surface of TNTAs. Whereas the diameter of the TNTAs exhibited a marginal increase with the increase in NH4F content [25]. During the anodization process, the growth of oxide thickness is due to the ion migration across the anodic film.…”
Section: Parametric Studymentioning
confidence: 95%
“…However, the higher percentage of NH4F reduced the length, which can be caused by the drastic chemical dissolution due to the increased number of fluoride ions on the surface of TNTAs. Whereas the diameter of the TNTAs exhibited a marginal increase with the increase in NH4F content [25]. During the anodization process, the growth of oxide thickness is due to the ion migration across the anodic film.…”
Section: Parametric Studymentioning
confidence: 95%
“…TiO 2 nanotubes prepared through electrochemical anodization have found wide applications in catalyst carriers, supercapacitors, biomedicine, and other cutting-edge fields. However, the formation mechanism of anodic TiO 2 nanotubes remains highly controversial. The classical field-assisted dissolution theory evolved from porous anodic alumina is still dominant. According to the field-assisted dissolution theory, the dissolution reaction of fluoride ions on titanium oxide is primarily responsible for pore formation in nanotubes. In recent years, new theories such as the viscous flow model, electric field equilibrium model, and oxygen bubble model have emerged, challenging the classical field-assisted dissolution theory. Traditional field-assisted dissolution theory fails to explain the three phases of the current–time curve or establish a relationship between the nanotube growth rate and the dissolution rate with respect to anodizing current. Despite emphasizing a balance between oxide growth and dissolution, few studies have reported on the growth rate and dissolution rate of TiO 2 nanotubes or examined their relationship with fluoride ion concentration. …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] However, the formation mechanism of the porous structure and nanotube structure of this kind of porous anodic oxide (PAO) is very controversial. 1,[12][13][14][15][16][17][18] Both formation mechanisms of PAA and anodic TiO 2 nanotubes include the eld-assisted dissolution (FAD), dissolution equilibrium, and eld-assisted ejection (FAE) theories and eld-assisted ow (FAF) model. 1,[19][20][21][22][23][24] There are currently two opposite models of pore formation in these PAOs.…”
Section: Introductionmentioning
confidence: 99%